Tennyson as an exponent of 19th century literature - Hood, Myrtle (My University, 1897)
Introduction: In writing an introduction to a subject of this nature, it seems necessary that one give a brief history of the literature of the nineteenth century. The closing years of the eighteenth (18th) century not only took from the world’s store of writers, but is also added to its list. The literature of those days was very different from anything which came before or anything that followed. A great change was noted in the ninth decade of the 18th century, and the writers who so bountifully added to the worlds’ store of knowledge, in the opening years of the present century were not what the world regarded them in after years. In this century a new form of poetry was given us and many of our loved poets belong to this age and time. Although it was not a poetical period yet it seems that poetry always took precedence of all other forms of literature.
Citation: Hood, Myrtle. Tennyson as an exponent of 19th century literature. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Tennyson; Literature; Poetry; English; 19th Century; Theses; Manuscripts (documents)